Iron bioavailability and utilization in rats fed cassava-based complementary diets - Onabanjo, O.O.; Maziya-Dixon, B.B.; Oguntona, C.R.B.; Olayiwola, I.O.; Oguntona, E.B.; Dixon, Alfred G.O. (International Institute of Tropical Agriculture, 2010)
Iron deficiency anaemia is still a major nutritional problem in the world, affecting primarily infants, children, and fertile women in both developing and developed countries (UNICEF, 2006). Breast-fed infants generally have adequate iron status during the first 4-6 mo of life, after which stored iron is depleted. Additional dietary iron therefore needs to be supplied. Improved cassava–based diets can provide a large proportion of the daily intake of energy and micronutrients for poor populations in many areas of sub-Saharan Africa. However, the bioavailability of these micronutrients especially iron is a concern as most of the iron contained in the foods is not available to the body. The study evaluated the bioavailability and utilization of iron in rats fed on iron improved cassava-based complementary diets. Iron bioavailability expressed as HRE was higher in the rats that consumed the positive control diet than in those fed with experimental diets. The study confirmed that the overall iron bioavailability from composite flour formulated from cassava is very low.